Adoption of AI technology in education among UTAR students: the case of Chatgpt - Heng, Wei Ni (2023)
AI has significantly affected various industries, including education. Nowadays, many universities have utilized ChatGPT to support staff and improve student learning experiences. This study will aim to investigate the factors that influence students’ adoption behavior on ChatGPT in their learning process and whether ChatGPT can improve their learning outcomes. Hence, the Unified Theory of Acceptance and Use of Technology (UTAUT) model was applied to investigate adoption of AI technology in education among UTAR students. Using the UTAUT model as a reference, performance expectancy, effort expectancy, social influence, perceived entertainment, perceived risk, adoption behavior, usage be the response. Six hypotheses were developed to identify the relationship between the variables. Questionnaires were prepared using Google Form and distributed to 200 respondents who had used ChatGPT in their learning process. The data collected from respondents were decoded and analysed by using SmartPLS version 4 software. Not only that, theoretical and managerial implications were proposed with the hope that future researchers and practitioners can serve as a reference for the experimental method to further understand students’ adoption behavior towards ChatGPT in their learning process.